Hypocalcemia in Covid-19: A Prognostic Marker for Severe Disease - Ahmad Raesi; Ebrahim Saedi Dezaki; Hamideh Moosapour; Farzaneh Saeidifard; Zahra Habibi; Fereidoun Rahmani; Soleiman Kheiri; Elham Taheri (Iranian Society of Pathology, 2020)
Background & Objective:  Previous studies have addressed the electrolyte abnormalitiessuch as hypocalcemiain COVID-19 patients. We aimed to compare the laboratory findings especially the electrolyte levels amongCOVID-19 patients and healthy controls and evaluate their prognostic values. Materials and Methods: This case-control study included 91 COVID-19 patients and 169 healthy individuals. Their laboratory parameters including electrolytes, albumin, liver enzymes, complete blood count, vitamin D, and parathyroid hormone (PTH) were compared. We also analyzed the association between these markers and the major outcomes including severity, mortality and hospitalization. Results: Among patients with COVID-19, 59.3% of the patients had hypocalcemia on admission while in control group only 32.5% had low calcium level (OR=3.02, 95% CI: 1.79-5.13, p <0.001). The rates of death and ICU admission were significantly higher among the patients in hypocalcemic group than those of eucalcemic group (85.7% vs 14.3% and 33.3% Vs 9.1%, respectively). However, there was no significant difference in the mean PTH and vitamin D levels between the two groups. In terms of the severity of the infection, 74.1% of patients in hypocalcemic group had a severe infection while 24.3% of the patients in eucalcemic group were diagnosed with severe infection (OR=8.89, 95% CI: 3.38-23.37, p <0.001). Conclusion: Patients with COVID-19 had considerable laboratory abnormalities including hypocalcemia. The hypocalcemia was also associated with worse major clinical outcomes and higher mortality risk.